Feasibility of on-Street Parking Based on Degree of Saturation - Cut Mutiawati; Lulusi Lulusi; Fitrika Mita Suryani; Sugiarto Sugiarto (Aceh International Journal of Science and Technology, 2018)
On-street parking leads to reduced road capacity and decreased traffic performance of the certain road. Therefore, this study was conducted to evaluate the feasibility of on-street parking based on road performance. The study was conducted at Central Business District namely Peunayong, Banda Aceh. Based on the Indonesian Highway Capacity Manual (IHCM) one of the performance parameter values is Degree of Saturation (DS). The data needed for calculation of DS are the geometric conditions, traffic volume and the side frictions. The results indicate that on-street parking facilities on segment 2 of Khairil Anwar Street should be evaluated, as the DS value is greater than 0.75 (unstable road condition), by changing parking patterns into a parallel configuration or eliminating parking facilities. Furthermore, the parking configuration of R.A. Kartini Street also needs to be rearranged. Despite the stable road performance, this road is uncomfortable to pass because there is only one lane remained due to unfeasible parking patterns and existence of street market along the segment. The road performance of Khairil Anwar Street (segment 1), Ahmad Yani Street, W.R Supratman Street, T.P. Polem Street, Twk. Daudsyah Street and Ratu Safiatuddin Street is in stable condition, with DS 0.75. This indicating that on-street parking facilities can be maintained. While as for the W.R. Supratman and Ahmad Yani Street should be evaluated in year of 2019 to avoid traffic jam along this corridors.